2002
DOI: 10.2214/ajr.178.1.1780047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vessel Size on Creation of Hepatic Radiofrequency Lesions in Pigs

Abstract: There appears to be a narrow transition zone for hepatic vessels at 2-4 mm, beyond which the heat sink effect was seen consistently and substantial vascular injury was rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
254
1
13

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(269 citation statements)
references
References 17 publications
1
254
1
13
Order By: Relevance
“…Portal vein thrombosis is a potentially fatal complication, with a 0.2% incidence [12] . Thrombosis and coagulation of vessels larger than 3 mm are rare when normal flow is granted [37] . Most of these thromboses are asymptomatic even in larger vessels and no further therapy is required [5,36] .…”
Section: Hepatic Vascular Damagementioning
confidence: 99%
“…Portal vein thrombosis is a potentially fatal complication, with a 0.2% incidence [12] . Thrombosis and coagulation of vessels larger than 3 mm are rare when normal flow is granted [37] . Most of these thromboses are asymptomatic even in larger vessels and no further therapy is required [5,36] .…”
Section: Hepatic Vascular Damagementioning
confidence: 99%
“…RFA is the treatment of choice for tumors less than 3 cm in size while TACE is used for tumors that exceed for 3 cm [Camma et al 2005;Livraghi et al 2000]. In addition, vessels can serve as a heat sink diminishing the effects of RFA, while proximity to other viscera can lead to extra-hepatic thermal injury [Livraghi et al 2003;Lu et al 2002] TACE is preferred in these cases. TACE cannot be performed in the presence of pre-existing portal vein thrombosis as it risks severely compromising the sole remaining hepatic blood supply, the hepatic artery.…”
Section: Locoregional Therapiesmentioning
confidence: 99%
“…One possible explanation for this discrepancy is that hepatic blood flow may have a cooling effect and could thus have influenced the ablative state in the clinical cases. By contrast, ex vivo bovine liver was not perfused with blood flow (17)(18)(19). Previous studies have demonstrated that a reduction in blood supply, such as in transcatheter arterial chemoembolization, results in enlarged ablative volume (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%